Identification and diversity or termite (Insecta: Isoptera) in oil palm plantation on peat soil in Sarawak, Malaysia - Kon, Thian Woei (2013)
Termites are the major decomposers in tropical region but yet their occurrences in oil palm plantation especially in peat soil are generally treated as pest. Three sampling plots of oil palm plantations in peat area with different years of palm establishment period were selected in the central region of Sarawak. These were Semanok (SM), Setuan (ST) and Sessang (SS), with years of oil palm establishment at 5-7, 6-8, 13-15 years in the sampling plot respectively. Modified belt transect sampling (50 × 6 m) was used to sample termites species. Soil block (25 × 25 × 30 cm) was collected from each of 10 points in a 50 × 50 m plot at SM site for soil macro-invertebrate study. Modified transect sampling had successfully sampled a total of 18 species of termites from 2 families (Rhinotermitidae and Termitidae), 5 subfamilies (Rhinotermitinae, Coptotermitinae, Termitinae, Macrotermitinae and Nasutitermitinae) and 11 genera (Coptotermes, Schedorhinotermes, Termes, Macrotermes, Nasutitermes, Globitermes, Amitermes, Parrhinotermes, Pericapritermes, Havilanditermes and Prohamitermes). A new species of genus Nasutitermes was found with close relationship with N. regularis. Highest species diversity was shown on site SS (H’= 2.118), followed by ST (H’= 2.048) and SM (H’= 2.002). SM and ST site shared the most similar species as compared to SS site. All plantation sites have termite dominantly feeding on rotten wood as a result of abundant dead woods in the peat soil after site clearing. This also brings the high species richness of wood-nester in SM and ST sites. Site SS had both wood nester and hypogeal nester being the highest nesting groups. Study also showed higher encounter of soil-feeding termite in longer established plantation. It indicates the gradual shifting of soil condition towards a stabilized environment which favours the successful settlement of soil feeder termite species. Results of soil invertebrate sampling in SM site showed highest species diversity in 0-10 cm layer of soil (H’= 2.25), followed by 10-20 cm (H’= 1.45) and 20-30 cm (H’= 0.74). While termite was significantly higher in relative density with increasing depth of soil (0-10 cm= 21.23%, 10-20 cm= 42.52% and 20-30 cm= 81.12%) which could be advantaged from being preyed by ants (Hymenoptera: Formicidae) which were higher in density from soil surface to 10 cm soil depth with relative density of 31.84%. Drained peat soil allowed the presence of soil invertebrates including termites, which also indicated their high tolerance to soil acidity. It is evident from this study that termite which had the ability to kill oil palm tree was attributed to Coptotermes curvignathus. Morphological study of distance of mandible tooth on worker termites showed significant difference among species under genus Coptotermes, Schedorhinotermes and Nasutitermes. Femur-tibia index also showed significant differences among species of genus Coptotermes, Schedorhinotermes and Nasutitermes. Hence, these new morphometric keys might be able to help differentiate termite which has similar morphological appearance. Molecular identification by mitochondrial DNA cytochrome oxidase II (COII) gene and 16S rRNA gene were shown to be able to identify termite species down to genus level. Identification down to species level depends on the availability of gene sequence deposited in the database. Nevertheless, the importance of conventional method shall not be ignored but to work out with molecular method for more convincing termite identification as well as to help in inferring phylogeny relationship of termite species.